Unusual migration of K-wire following fixation of clavicle fracture: a case report - (:unkn) unknown (TURKISH ASSOC TRAUMA EMERGENCY SURGERY, 2009)
The migration of various internal fixation devices, especially Kirshner (K) wires, is well established. The wires usually follow a retrograde path, protruding near the entry point. When they migrate in the other direction, serious problems may occur. Migration of K-wires to the lung, heart, spleen, subclavian artery, pulmonary artery and aorta have been reported in a few cases. A 26-year-old male with chest pain was seen in our clinic. The patient had been operated for left distal clavicle fracture two years before. No abnormality was noted on the physical examination. Radiographs showed migration of the wire outside the clavicle across the sternum to the opposite hemithorax. The pin was removed through the incision over the sternum under direct vision with thoracoscope. The pin was extrapleurally located. There was no additional morbidity attributed to thoracoscopy or chest tube. In conclusion, K-wires can easily migrate, resulting in serious complications. Close follow-up should be done after internal fixation.
Keywords: Acromioclavicular joint; fracture/fixation; Kirshner wire; migration; shoulder; KIRSCHNER WIRE; ACROMIOCLAVICULAR JOINT; PIN